Application of agromarketing by Ukrainian enterprises and farmers - Suslo, Vitalii (2024)
The thesis investigates the application of agromarketing by Ukrainian enterprises and farmers as a means to enhance competitiveness, profitability, and sustainability. The research explores essential strategies such as digital marketing, direct sales, and precision agriculture within the context of Ukraine's agricultural landscape. It examines challenges influencing factors that lower rates of agromarkting implementation such as geopolitical tensions, financial constraints, and low customer engagement, while also recognizing opportunities in imlpementation of agromarketing. Utilizing expert interviews and stakeholder surveys, the study highlights the advantages of agromarketing, which include improved market access and strengthened customer relationships, alongside obstacles such as outdated infrastructure and limited digital integration. The conclusions drawn from the findings offer recommendations for optimizing agromarketing practices to align with the changing demands of the market.